Nonavalent HPV vaccine - Marília Barcelos Marqui; Aislan Cristina Rheder Fagundes Pascoal; Luana Tiuma Borba; Luiza de Souza Duarte; Vinicius D’Ávila Bitencourt Pascoal; Fabiana Nunes Germano (DST, 2022)
Sexually transmitted infections caused by the human papillomavirus (HPV) are the most prevalent in the world and can cause from genital warts to premalignant lesions, which can lead to cervical cancer, vaginal and vulvar neoplasms, anal and penile cancer, if left untreated. Non-genital pathologies may also be related to HPV, such as oropharyngeal cancer and recurrent respiratory papillomatosis(1-3). HPV can be transmitted whenever there is direct contact of infected hair and mucosa during sexual intercourse. It can also occur via the maternal fetal route (pregnancy, intra and peripartum)(4). The lesions are imperceptible in many cases, without manifestations of infection, which may facilitate transmission. [...]